ANALISIS DETERMINAN PENDAPATAN ASLI DAERAH WILAYAH TAPAL KUDA - Liska Liska (JEP (Jurnal Ekonomi Pembangunan), 2020)
The regional development process is the most important thing in the community economy. Therefore economic development is a regional economic success. With the existence of regional development, it shows the success of local revenue. This study aims to determine how much influence the independent variables have on the dependent variable. This type of research is explanatory which aims to explain the relationship between the independent variables and the dependent variable. The independent variables in this study are investment, population, development revenue. While the dependent variable is in the form of Regional Original Income in the Horseshoe Region of East Java. The method used in this research is panel data regression with the Fixed Effect Model (FEM) approach. Based on the research results, it shows that investment has a positive and significant effect on Regional Original Income. Total Population has a positive and significant effect on Regional Original Income. Development revenue has a positive and significant effect on Regional Original Income.